2016
DOI: 10.1002/met.1560
|View full text |Cite
|
Sign up to set email alerts
|

A persistent wintertime fog episode at Lisbon airport (Portugal): performance of ECMWF and AROME models

Abstract: ABSTRACT:The 7-8 January 2015 persistent fog episode at Lisbon international airport is analysed. Its persistence was atypical of the local climate (second longest episode since 2004) and caused significant air traffic disruptions. Furthermore, the performance of two operational models (European Centre for Medium-range Weather Forecasts (ECMWF) and Applications of Research to Operations at Mesoscale (AROME)) used at the Portuguese Weather Service is assessed not only for the selected fog episode, but also for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The calculated SAR of water was high (35.4) but tolerated by halophyte species (Haro et al, 1993;Flowers and Colmer, 2008; Table 2). The maritime fog mostly observed from November to February each year in the Lisbon area (Belo-Pereira and Santos, 2016), is deposited as occult precipitation by condensing or sublimating directly onto plant surfaces (Karavoltsos et al, 2017), probably contributing to the water balance of plants in these saline habitats. After plant growth (T3), the soils irrigated with brackish water show no change in pH values, however the EC values of FLU (5.6 dS/m) and TEC (5.9 dS/m) had a significant (p < 1 × 10 −7 ) increase (34.03; 32.48 dS/m, respectively) due to the high salinity of estuarine water.…”
Section: Characterization Of Soils Amendments and Irrigation Watermentioning
confidence: 99%
“…The calculated SAR of water was high (35.4) but tolerated by halophyte species (Haro et al, 1993;Flowers and Colmer, 2008; Table 2). The maritime fog mostly observed from November to February each year in the Lisbon area (Belo-Pereira and Santos, 2016), is deposited as occult precipitation by condensing or sublimating directly onto plant surfaces (Karavoltsos et al, 2017), probably contributing to the water balance of plants in these saline habitats. After plant growth (T3), the soils irrigated with brackish water show no change in pH values, however the EC values of FLU (5.6 dS/m) and TEC (5.9 dS/m) had a significant (p < 1 × 10 −7 ) increase (34.03; 32.48 dS/m, respectively) due to the high salinity of estuarine water.…”
Section: Characterization Of Soils Amendments and Irrigation Watermentioning
confidence: 99%
“…The scientific community has developed various approaches for fog forecasting. Numerical weather prediction (NWP) models are widely used for fog prediction, but accuracy is still unsatisfactory (Belo-Pereira and Santos [2]). The adequate representation of the atmosphere physics in the lower part of the troposphere and the interaction with the land surface remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Among the weather phenomena that affect the visibility range near the Earth's surface, fog is the one that constrains human activities with most economic impact, and sometimes even jeopardizes human lives. Due to its great incidence on aviation, climatological studies and field campaigns have been focused on busy airports around the world [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The World Meteorological Organization defines fog as the visibility restriction due to water droplets in the lower atmosphere that reduces the horizontal visibility to less than 1 km near to the ground [8]. The knowledge of local weather conditions that culminate in fog plays a major role in operational forecast [1]. A study carried out by Policarpo et al [9] has shown that a large artificial lake of 250 km 2 and its irrigated area become a local important source of moisture, that increases the availability of water vapour, favouring the formation of fog over the lake and its surroundings.…”
Section: Introductionmentioning
confidence: 99%